Prospective multicentre cohort study of patient-reported outcomes and complications following major abdominal neoplastic surgery (PATRONUS) - study protocol for a CHIR-Net student-initiated German medical audit study (CHIR-Net SIGMA study) - Fink, Christoph Andreas; Friedrich, Mirco; Frey, Pia-Elena; Rädeker, Lukas; Leuck, Alexander; Bruckner, Thomas; Feißt, Manuel; Tenckhoff, Solveig; Klose, Christina; Dörr-Harim, Colette; Mihaljevic, André Leopold (BMC surgery, 2018)
One of the most important aspects of designing a clinical trial is selecting appropriate outcomes. Patient-reported outcomes (PROs) can provide a personal assessment of the burden and impact of a malignant disease and its treatment. PROs comprise a wide range of outcomes including basic clinical symptom scores and complex metrics such as health-related quality of life (HRQoL). There is limited data on how postoperative complications following cancer surgery affect symptoms and HRQoL. For this reason the primary aim of the PATRONUS study is to investigate how perioperative complications affect cancer-related symptoms and HRQoL in patients undergoing abdominal cancer surgery. The PATRONUS study is designed and will be initiated and conducted by medical students under the direct supervision of clinician scientists based on the concept of inquiry-based learning.
Gesehen am 05.12.2018